Pituitary stalk interruption syndrome and liver cirrhosis associated with diabetes and an inactivating KCNJ11 gene mutation: a case report and literature review - Liu, Zhaoxiang; Zhao, Wenhui; Cao, Chenxiang; Wang, Yanlei; Xiao, Luqi; Wang, Xiaojing; Jin, Chenxi; Xiao, Jianzhong (Frontiers in Endocrinology, 2023)
Background: Pituitary stalk interruption syndrome (PSIS) is a congenital disease commonly found in patients with combined pituitary hormone deficiency (CPHD).Most PSIS patients manifest growth retardation and delayed puberty. We reported a rare case of PSIS with tall stature, liver cirrhosis and diabetes, possibly caused by an inactivating KCNJ11 gene mutation. Case presentation: A 37-year-old female patient initially presented with liver cirrhosis and diabetes, without any secondary sexual characteristics. Endocrine investigation indicated CPHD. Small anterior pituitary, A lack of invisible pituitary stalk and no eutopic posterior lobe hypersignal in the sella turcica viewed in magnetic resonance imaging (MRI) confirmed the diagnosis of PSIS. Despite receiving no growth hormone or sex hormone therapy, she reached a final height of 186 cm. Liver histopathology revealed nonalcoholic fatty cirrhosis. Genetic testing identified a heterozygous p.Arg301Cys mutation in the KCNJ11 gene. Conclusions: This is a rare case of PSIS with liver cirrhosis and diabetes associated with an inactivating KCNJ11 gene mutation. It's supposed that early hyperinsulinism caused by the KCNJ11 gene mutation, as well as delayed epiphyseal closure due to estrogen deficiency, contributed to the patient's exceptionally tall stature. Untreated growth hormone deficiency (GHD) resulted in increased visceral fat, leading to nonalcoholic fatty liver disease (NAFLD) and cirrhosis. The decline in β cell function with age, combined with NAFLD, may have played a role in the development of diabetes.